Oxygen vacancy-containing transition metal hydroxide electrode material and preparation method thereof
By growing zeolite imidazole ester skeleton material in situ on nickel foam and soaking nickel-cobalt inorganic salt and reducing sodium borohydride, transition metal hydroxide electrode materials containing oxygen vacancies are prepared, and the electrode materials in the prior art are solved at high power in the current technology The problem of low energy density under density has achieved the construction of rich pore structures and stable vacancy, which has significantly improved the electrochemical performance.
Patent Information
- Application Number
- CN202411592881.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-03
AI Technical Summary
The existing transition metal hydroxide electrode materials have low energy density at high power density, making it difficult to meet the requirements of high-performance capacitors, and the simple array structure has problems of poor conductivity and low surface area.
By growing the zeolite imidazole ester skeleton material Co-ZIF-L in situ on nickel foam, immersed with nickel-cobalt inorganic salt and reducing sodium borohydride solution, the transition metal hydroxide electrode material Ov-NiCoOH with oxygen-containing vacant positions is prepared to form rich The pore structure and stable vacancy improve charge transfer efficiency.
The energy density and power density of the electrode material are significantly improved, especially at extremely high power density, which can still maintain a high energy density, improve electrochemical performance, especially in terms of magnification.
Smart Images

Figure CN119252675A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrode materials, and in particular to a transition metal hydroxide electrode material containing oxygen vacancies and a preparation method thereof. Background Art
[0002] Electrodes are the core part of energy storage components. In supercapacitors, electrodes are one of the key components to improve their energy density and rate performance. Supercapacitors can charge and discharge quickly, making them very suitable for use in applications that require high power density. Transition metal compounds (Co, Ni, Fe, etc.) have the advantages of low cost, environmental friendliness, and large theoretical capacity, making them ideal electrode materials for electrochemical energy storage devices. However, simple array structures often have problems such as poor conductivity, low surface area, and limited electrochemical active sites, which hinder their future applications.
[0003] Although the simple construction of vacancies can improve the conductivity of the material to enhance the rate performance and energy density, the assembled supercapacitor has a low energy density at a higher power density and cannot meet the requirements of high-performance capacitor junction electrode materials. There are few reports in the literature on supercapacitor devices that test the energy density at a high power density of 20,000 W / kg. Summary of the invention
[0004] The purpose of the present invention is to solve the above-mentioned problems in the prior art and to provide a transition metal hydroxide electrode material containing oxygen vacancies and a preparation method thereof, which promotes the rapid transmission of charges through rich pore structure and stable oxygen vacancies, greatly improves the energy density and power density of the electrode material, and enables it to maintain a certain energy density (21.7 Wh / kg) at an extremely high power density (52000 W / kg).
[0005] In order to achieve the above object, the present invention adopts the following technical scheme:
[0006] A method for preparing a transition metal hydroxide electrode material containing oxygen vacancies comprises the following steps:
[0007] 1) In situ growth of zeolite imidazolate framework material Co-ZIF-L on nickel foam;
[0008] 2) Co-ZIF-L was soaked in nickel-cobalt inorganic salts to exchange ligands to obtain NiCoOH;
[0009] 3) NiCoOH is reduced with sodium borohydride solution to obtain the transition metal hydroxide electrode material Ov-NiCoOH containing oxygen vacancies.
[0010] In step 1), cobalt salt is dissolved in water to obtain solution A, dimethylimidazole is dissolved in water to obtain solution B, solution B is poured into solution A and stirred evenly to obtain solution C, and nickel foam is placed in solution C for self-growth to obtain the Co-ZIF-L.
[0011] In step 1), the concentration of cobalt salt is 0.7~1 mol / L, and the concentration of dimethylimidazole is 12~16 mol / L.
[0012] The self-growth time is 2 to 6 hours.
[0013] In step 2), Co-ZIF-L is immersed in an aqueous solution containing cobalt salt and nickel salt to obtain the NiCoOH.
[0014] In step 2), in the aqueous solution containing cobalt salt and nickel salt, the concentration of cobalt salt is not higher than 1.5 mol / L, and the concentration of nickel salt is not higher than 1.5 mol / L.
[0015] In step 2), the soaking time is 6 to 24 hours.
[0016] In step 3), the concentration of the sodium borohydride solution is 1-4 mol / L, and the reduction reaction time is no longer than 60 min.
[0017] In the present invention, the cobalt salt is an inorganic cobalt salt such as nitrate, carbonate, sulfate, etc.; the nickel salt is an inorganic nickel salt such as nitrate, carbonate, sulfate, etc.
[0018] The transition metal hydroxide electrode material containing oxygen vacancies described in the present invention is prepared by the above method and is an Ov-NiCoOH electrode material containing rich pore structure and appropriate and stable vacancies.
[0019] The application of the transition metal hydroxide electrode material containing oxygen vacancies is used for electrochemical energy storage materials, especially for supercapacitor energy storage electrodes.
[0020] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0021] In the method of the present invention, the self-assembled Co-ZIF-L material is etched at room temperature to obtain NiCoOH containing a rich pore structure, and then Ov-NiCoOH containing an appropriate amount of stable vacancies is obtained by adjusting the reduction time of the sodium borohydride solution at room temperature. Relying on the pore structure and vacancies, the material surface has abundant electrochemical active sites, which reduces the charge transfer resistance and greatly improves the electrochemical performance of the material, especially in terms of rate. Therefore, the present invention has broad application prospects in the field of high-performance supercapacitor electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 11 to 4 are X-ray diffraction (XRD) patterns of Examples 1 to 4.
[0023] Figure 2 The scanning electron microscope (SEM) images of Examples 1 to 4 are shown.
[0024] Figure 3 In the figure, Figure a is the TEM image of Example 1, Figure b is its HAADF-STEM element distribution image, Figure c is the HRTEM image of Example 1, and Figure d is its diffraction ring image.
[0025] Figure 4 The electron paramagnetic resonance (EPR) images of Examples 1 and 2 are shown in FIG.
[0026] Figure 5 Comparison of cyclic voltammetry (CV) curves of Examples 1 to 4 at a scan rate of 10 mV / s.
[0027] Figure 6 Comparison of constant current charge and discharge (GCD) curves of Examples 1 to 4 at a current density of 1 A / g.
[0028] Figure 7 The figure is a comparison of the rate performance of Examples 1 to 4.
[0029] Figure 8 Comparison of Nyquist electrochemical impedance spectroscopy (EIS) of Examples 1 to 4.
[0030] Fig. 9 This is the constant current charge and discharge (GCD) curve of the supercapacitor 20Ov-NiCoOH / / AC assembled in Example 1 at a current density of 1 to 65 A / g.
[0031] Fig.10 Cyclic stability test of the supercapacitor 20Ov-NiCoOH / / AC assembled in Example 1. DETAILED DESCRIPTION
[0032] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0033] Example 1
[0034] A certain amount of cobalt nitrate is dissolved in an appropriate amount of water to obtain solution A (cobalt nitrate concentration 0.7 mol / L), and then an appropriate amount of dimethylimidazole is dissolved in an appropriate amount of water to obtain solution B (dimethylimidazole concentration 12 mol / L). Solution B is poured into solution A and stirred evenly to obtain solution C. The washed nickel foam is placed in solution C to obtain the precursor Co-ZIF-L (reaction time is 3 h). The obtained Co-ZIF-L is soaked in an aqueous solution containing cobalt chloride and nickel chloride (cobalt chloride concentration is 0.75 mol / L, nickel chloride concentration is 0.75 mol / L) to obtain NiCoOH. Finally, NiCoOH is placed in a sodium borohydride aqueous solution (sodium borohydride solution concentration is 1 mol / L, reaction time is 20 min) for reduction to obtain the electrode material 20Ov-NiCoOH.
[0035] Evaluation of the electrochemical properties of the electrode materials: At room temperature, in a three-electrode test system assembled with the material prepared in Example 1 as the working electrode, mercury oxide electrode as the reference electrode, graphite rod electrode as the counter electrode and 6 mol / L KOH solution as the electrolyte, the working electrode has a high specific capacitance of 255 mAh / g and excellent rate performance of 95% (10 A / g), 84.7% (100 A / g), and 69.8% (230 A / g).
[0036] Example 2
[0037] The difference between Example 2 and Example 1 is that no sodium borohydride reduction is performed to obtain the electrode material NiCoOH.
[0038] Evaluation of the electrochemical properties of the electrode materials: At room temperature, in the three-electrode test system assembled in Example 1, the working electrode had a specific capacitance of 155 mAh / g and rate performances of 88% (10 A / g), 74% (100 A / g), and 58% (130 A / g).
[0039] Example 3
[0040] Compared with Example 1, the difference between Example 3 and Example 1 is that the reaction time of the sodium borohydride aqueous solution is 10 min, and the electrode material 10Ov-NiCoOH is obtained by reduction.
[0041] Evaluation of the electrochemical properties of the electrode materials: At room temperature, in the three-electrode test system assembled in Example 1, the working electrode had a high specific capacitance of 214 mAh / g and rate performances of 95% (10 A / g), 77.9% (100 A / g), and 59% (200 A / g).
[0042] Example 4
[0043] Compared with Example 1, the difference between Example 4 and Example 1 is that the reaction time of the sodium borohydride aqueous solution is 30 min, and the electrode material 30Ov-NiCoOH is obtained by reduction.
[0044] Evaluation of the electrochemical properties of the electrode materials: At room temperature, in the three-electrode test system assembled in Example 1, the working electrode had a high specific capacitance of 215 mAh / g and rate performances of 93% (10 A / g), 77.4% (100 A / g), and 55.8% (150 A / g).
[0045] Comparative Example 1
[0046] Compared with Example 1, the difference between Comparative Example 1 and Example 1 is that Co-ZIF-L is immersed in an aqueous solution containing cobalt chloride (cobalt chloride concentration is 1.5 mol / L) to obtain Co(OH)2, but it is not reduced by sodium borohydride solution.
[0047] Evaluation of the electrochemical properties of the electrode materials: At room temperature, in the three-electrode test system assembled in Example 1, the working electrode had a specific capacitance of 63 mAh / g and a rate performance of 76% (10 A / g) and 53% (30 A / g).
[0048] Comparative Example 2
[0049] Compared with Example 1, the difference between Comparative Example 2 and Example 1 is that Co-ZIF-L is immersed in an aqueous solution containing cobalt chloride and nickel chloride (cobalt chloride concentration is 1 mol / L, nickel chloride concentration is 0.5 mol / L) to obtain NiCoOH-1, but it is not reduced by sodium borohydride solution.
[0050] Evaluation of the electrochemical properties of the electrode materials: At room temperature, in the three-electrode test system assembled in Example 1, the working electrode had a specific capacitance of 110 mAh / g and rate performance of 74% (10 A / g) and 59% (30 A / g).
[0051] Comparative Example 3
[0052] Compared with Example 1, the difference between this Comparative Example 3 is that Co-ZIF-L is immersed in an aqueous solution containing cobalt chloride and nickel chloride (cobalt chloride concentration is 0.5 mol / L, nickel chloride concentration is 1 mol / L) to obtain NiCoOH-2, but it is not reduced by sodium borohydride solution.
[0053] Evaluation of the electrochemical performance of the electrode material: At room temperature, in the three-electrode test system assembled in Example 1, the working electrode had a specific capacitance of 125 mAh / g and a rate performance of 48% (10 A / g).
[0054] Comparative Example 4
[0055] Compared with Example 1, the difference between Comparative Example 4 and Example 1 is that Co-ZIF-L is immersed in deionized water to obtain Co(OH)2-1, but it is not reduced by sodium borohydride solution.
[0056] Evaluation of the electrochemical performance of the electrode material: At room temperature, in the three-electrode test system assembled in Example 1, the working electrode had a specific capacitance of 29 mAh / g and rate performance of 82% (10 A / g) and 51% (30 A / g).
[0057] Comparative Example 5
[0058] Compared with Example 1, the difference between Comparative Example 5 and Example 1 is that Co-ZIF-L is immersed in an aqueous solution containing nickel chloride (nickel chloride concentration is 1.5 mol / L) to obtain NiCoOH-3, but it is not reduced by sodium borohydride solution.
[0059] Evaluation of the electrochemical performance of the electrode material: At room temperature, in the three-electrode test system assembled in Example 1, the working electrode had a specific capacitance of 80 mAh / g and a rate performance of 50% (10 A / g).
[0060] Figure 1 1 is the X-ray diffraction (XRD) diagram of Examples 1 to 4 of the present invention.
[0061] like Figure 1 In a, the peaks at 11.35°, 22.74°, 33.46°, 38.77°, and 61.25° correspond to the (003), (006), (101), (015), and (113) crystal planes of NiCoOH prepared in Example 2 (PDF#00-038-0715). Figure 1 As can be seen in b, compared with the sample in Example 2, the peak intensities of the (006) and (015) planes of Examples 1, 3 and 4 gradually decrease, indicating that sodium borohydride reduction causes a decrease in crystallinity and may introduce surface defects.
[0062] Figure 2 The scanning electron microscope (SEM) images of Example 1 and Examples 2 to 4 of the present invention are shown.
[0063] like Figure 2 Figure a is the SEM image of NiCoOH prepared in Example 2, which shows an interlaced nanosheet structure, Figure b is the SEM image of 10Ov-NiCoOH prepared in Example 3, Figure c is the SEM image of 20Ov-NiCoOH prepared in Example 1, and Figure d is the SEM image of 30Ov-NiCoOH prepared in Example 4. Compared with Example 2, wrinkles appear on the surface, and the surface of Example 4 begins to be damaged.
[0064] Figure 3 Figure a is a TEM image of Example 1, Figure b is a HAADF-STEM element distribution image, Figure c is a HRTEM image of Example 1, and Figure d is its diffraction ring image;
[0065] from Figure 3 In Figure a, many pore structures can be observed. Figure 3 In b, we can see that Ni, Co and O are evenly distributed in the material (blue marks represent O, red marks represent CO, and green marks represent Ni). Figure 3 The lattice fringes in c are measured to be 0.232 nm, corresponding to the (015) crystal plane of NiCoOH, and obvious lattice defects are observed on its surface, indicating the successful construction of defects. Figure 3 The two concentric radii of the diffraction ring in d correspond to the (110) and (015) crystal planes of the material.
[0066] Figure 4 The electron paramagnetic resonance (EPR) spectra of Examples 1 and 2 of the present invention are shown.
[0067] Depend on Figure 4 It can be seen that the 20Ov-NiCoOH prepared in Example 1 has a signal peak at g = 2.001, while the NiCoOH prepared in Example 2 has no obvious peak signal. It can be concluded that the reduction of sodium borohydride causes oxygen vacancies in the material.
[0068] Figure 5 Comparison of cyclic voltammetry (CV) curves of Examples 1 to 4 of the present invention at a scan rate of 10 mV / s.
[0069] from Figure 5 From the CV curves of the four electrodes at a constant scan rate of 10 mV / s, it can be seen that the electrodes all exhibit the characteristics of typical battery-type materials. In addition, the potential difference between the oxidation peak and the reduction peak of the 20Ov-NiCoOH electrode prepared in Example 1 (ΔE = 0.15 V) is the smallest, and the reversibility is the largest. Compared with other electrodes, the 20Ov-NiCoOH electrode has the largest closed geometric area, which means that the 20Ov-NiCoOH electrode has the highest specific capacitance.
[0070] Figure 6 The constant current charge and discharge (GCD) curves of Examples 1 to 4 of the present invention are compared at a current density of 1 A / g.
[0071] Depend on Figure 6It can be seen that the GCD curve of 20Ov-NiCoOH is basically symmetrical, indicating that it has a high coulombic efficiency and a certain reversible behavior. And there is a certain charge and discharge platform in the GCD curve, indicating that the electrochemical process is jointly determined by diffusion control and surface control. In addition, according to the discharge time, at a current density of 1 A / g, the 20Ov-NiCoOH electrode has a specific capacitance of 255 mAh / g, which is higher than 155 mAh / g of NiCoOH electrode, 214 mAh / g of 10Ov-NiCoOH electrode and 215 mAh / g of 30Ov-NiCoOH electrode.
[0072] Figure 7 The figure is a comparison of the rate performance of Example 1 and Examples 2 to 4 of the present invention;
[0073] Depend on Figure 7 It can be seen that from the initial 1 A·g -1 At a current density of 10 A / g, the capacitance retention rate of the 20Ov-NiCoOH electrode is 95%. At an ultra-high current density of 230 A / g, the 20Ov-NiCoOH electrode still retains 69.8% of its capacitance, reflecting the good rate performance of the 20Ov-NiCoOH electrode material.
[0074] Figure 8 The Nyquist electrochemical impedance spectroscopy (EIS) comparison of Examples 1 to 4 of the present invention.
[0075] Depend on Figure 8 It can be seen that the Nyquist plot consists of a semicircle in the high- and medium-frequency region and a slant line in the low-frequency region. According to the test results, 20Ov-NiCoOH (R ct = 0.14 Ω) is significantly smaller than NiCoOH (R ct = 1.59 Ω), 10Ov-NiCoOH (R ct = 0.34 Ω) and 30Ov-NiCoOH2 (R ct = 0.79 Ω), indicating that the 20Ov-NiCoOH electrode has the fastest electron transfer rate. In addition, the 20Ov-NiCoOH has the largest linear slope in the low-frequency region, showing the largest K + / OH - Ion diffusion coefficient. Minimum charge transfer resistance and maximum ion diffusion coefficient make redox reactions more likely to occur, indicating that reasonable regulation of vacancies can provide abundant and stable electrolyte active centers, which is beneficial to improving electrical conductivity and promoting rapid ion diffusion rate.
[0076] In the present invention, 20Ov-NiCoOH is used as a supercapacitor positive electrode, AC (activated carbon) is used as a negative electrode, and 6 M KOH aqueous solution is used as an electrolyte, and they are assembled together into a supercapacitor for a double-electrode electrochemical performance test. The assembled supercapacitor is recorded as 20Ov-NiCoOH / / AC.
[0077] Fig. 9 This is the constant current charge and discharge (GCD) curve of the supercapacitor 20Ov-NiCoOH / / AC assembled in Example 1 of the present invention at a current density of 1 ~65 10A / g.
[0078] Depend on Fig. 9 It can be seen that the 20Ov-NiCoOH / / AC supercapacitor has extremely superior rate performance, with an energy density of 48.2 Wh / kg at a power density of 800 W / kg, and even at an ultra-high power density of 52000 W / kg, it still maintains an energy density of 21.7 Wh / kg.
[0079] Fig.10 This is a cycle stability test of the supercapacitor 20Ov-NiCoOH / / AC assembled in Example 1 of the present invention.
[0080] Depend on Fig.10 It can be seen that the 20Ov-NiCoOH / / AC supercapacitor has an excellent number of cycles. After 5000 continuous charge and discharge cycles at a high current density of 30 A / g, it still retains 91.5% of the initial capacitance, indicating that 20Ov-NiCoOH / / AC has excellent reversibility and cycle stability. At the same time, it also has almost 100% Coulomb efficiency in 5000 cycles, which again shows that it has a certain degree of reversibility.
[0081] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for preparing a transition metal hydroxide electrode material containing oxygen vacancies, characterized in that: The following steps are involved: 1) In situ growth of zeolite imidazolate framework material Co-ZIF-L on nickel foam; 2) Co-ZIF-L was soaked in nickel-cobalt inorganic salts to exchange ligands to obtain NiCoOH; 3) NiCoOH is reduced with sodium borohydride solution to obtain the transition metal hydroxide electrode material Ov-NiCoOH containing oxygen vacancies.
2. The method for preparing a transition metal hydroxide electrode material containing oxygen vacancies according to claim 1, characterized in that: In step 1), cobalt salt is dissolved in water to obtain solution A, dimethylimidazole is dissolved in water to obtain solution B, solution B is poured into solution A and stirred evenly to obtain solution C, and nickel foam is placed in solution C for self-growth to obtain the Co-ZIF-L.
3. The method for preparing a transition metal hydroxide electrode material containing oxygen vacancies according to claim 2, characterized in that: In step 1), the concentration of cobalt salt is 0.7~1 mol / L, and the concentration of dimethylimidazole is 12~16 mol / L.
4. The method for preparing a transition metal hydroxide electrode material containing oxygen vacancies according to claim 2, characterized in that: The self-growth time is 2 to 6 hours.
5. The method for preparing a transition metal hydroxide electrode material containing oxygen vacancies according to claim 1, characterized in that: In step 2), Co-ZIF-L is immersed in an aqueous solution containing cobalt salt and nickel salt to obtain the NiCoOH.
6. The method for preparing a transition metal hydroxide electrode material containing oxygen vacancies according to claim 5, characterized in that: In step 2), in the aqueous solution containing cobalt salt and nickel salt, the concentration of cobalt salt is not higher than 1.5 mol / L, and the concentration of nickel salt is not higher than 1.5 mol / L.
7. The method for preparing a transition metal hydroxide electrode material containing oxygen vacancies according to claim 5, characterized in that: In step 2), the soaking time is 6 to 24 hours.
8. The method for preparing a transition metal hydroxide electrode material containing oxygen vacancies according to claim 1, characterized in that: In step 3), the concentration of the sodium borohydride solution is 1-4 mol / L, and the reduction reaction time is no longer than 60 min.
9. A transition metal hydroxide electrode material containing oxygen vacancies, characterized in that: Prepared by any one of the preparation methods of claims 1 to 8.
10. The use of a transition metal hydroxide electrode material containing oxygen vacancies according to claim 9, characterized in that: Used in electrochemical energy storage materials, especially in supercapacitor energy storage electrodes.
